RNA-Seq Profiling Shows Divergent Gene Expression Patterns in Arabidopsis Grown under Different Densities - Guo, Di; Song, Xiaoming; Yuan, Min; Wang, Zhenyi; Ge, Weina; Wang, Li; Wang, Jinpeng; Wang, Xiyin (Frontiers in Plant Science, 2017)
Plants growing under high-density conditions experience increased competition for water, nutrients, and light, possibly leading to changes in size, biomass, morphology, and productivity. However, no research has focused on the relationship between whole-genome expression patterns and growth density. Here, we performed whole-genome RNA sequencing to examine the gene expression patterns in Arabidopsis grown under low and high densities. Of the 20,660 detected genes, the expression levels of 98 were enhanced and 107 were repressed under high-density growth. Further analysis revealed that changes in density influenced metabolism- and stimulus-related genes the most. Furthermore, high-density growth led to a shade avoidance phenotype, represented by upward growth and a reduction in rosette leaves. Moreover, a cluster of glutaredoxin genes, GRXS3, 4, 5, 7, and 8, were significantly down-regulated under high density, suggesting that high density affects plant growth mainly by nitrate limitation.